Pengumuman Perhitungan Baru Indeks LQ45 dan IDX30: Apakah Ada Reaksi pada Pasar Modal Indonesia? - Rizal Agus Bimantara; Ely Siswanto; Yuli Soesetio (Faculty of Economic and Business, 2019)
This study discusses whether there an influence from the announcement of the newcalculation of LQ45 and IDX30 index. This study uses indicators of abnormal return, cumulative abnormal return, and trading volume activity as a measure of market reaction. The population of this study is the companies incorporated in the IDX30 index. The sampling method uses purposive sampling method and obtained sample of 20 companies.The window period in this study is 11 days. Statistical tests using paired sample t-test and Wilcoxon sign rank test. The results of this study indicate there are no differences in the average abnormal return and trading volume activity before and after the event. There are differences in cumulative abnormal returns before and after events. This shows that investors have anticipated the news and the market has adjusted to a new balance before the announcement of the new LQ45 and IDX30 index calculations officially applied.